2018
DOI: 10.1016/j.placenta.2017.11.013
|View full text |Cite
|
Sign up to set email alerts
|

New imaging markers for preconceptional and first-trimester utero-placental vascularization

Abstract: Preconceptional and first-trimester 3D PD ultrasound utero-placental and embryonic vascular volume measurements using VR are feasible and reliable. Longitudinal cohort studies with repeated measurements are needed to further validate this and assess their value as new imaging markers for placental vascular development and ultimately for the prediction of placenta-related pregnancy complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(44 citation statements)
references
References 24 publications
0
38
0
Order By: Relevance
“…A newly developed technique is Virtual Reality (VR) which can be combined with measurements of 3D power Doppler (PD) ultrasound volumes and visualizes the placental circulation from early pregnancy onward, in three dimensions with depth perception. As previously demonstrated by Reijnders et al (2018) this technique is feasible and reliable for use in the first trimester of pregnancy to measure placental parameters, that reflect PV and uteroplacental vascularization of the uterine/maternal side (i.e., the placental bed).…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…A newly developed technique is Virtual Reality (VR) which can be combined with measurements of 3D power Doppler (PD) ultrasound volumes and visualizes the placental circulation from early pregnancy onward, in three dimensions with depth perception. As previously demonstrated by Reijnders et al (2018) this technique is feasible and reliable for use in the first trimester of pregnancy to measure placental parameters, that reflect PV and uteroplacental vascularization of the uterine/maternal side (i.e., the placental bed).…”
Section: Introductionmentioning
confidence: 85%
“…To minimize artifacts and measurement errors by movement, participants were asked to hold their breath for approximately 30 s during image acquisition. All ultrasound examinations were performed according to international guidelines on safe use of Doppler ultrasound in the first trimester of pregnancy (ALARA-principle) and, as such, total scanning time was kept as low as possible with a maximal duration of 30 min and a maximal thermal index of 1.3 (The British Medical Ultrasound Society, 2009;Bhide et al, 2013;World Federation For Ultrasound in Medicine and Biology, 2013;Reijnders et al, 2018).…”
Section: Ultrasoundmentioning
confidence: 99%
See 1 more Smart Citation
“…By assessing these 3D datasets in an innovative virtual reality system (Barco I-Space or 3D desktop), depth perception and three-dimensional interaction enables more accurate and detailed quantification of the utero(placental) vascular volumes. At the Erasmus MC, there is extensive experience with this novel technology and the uteroplacental vascular volume measurements have proven to be feasible and reliable 45 46…”
Section: Study Procedures/measurementsmentioning
confidence: 99%
“…12 A high intraobserver and interobserver reproducibility and its potential interest for placental function study were reported by our team. [13][14][15] The main limit of this technique is that the calculated 3DPD indices are dependent on different physiological parameters (such as body mass index (BMI), placenta location) and machine settings. This has been proved in vitro, and it is also considered as a main cause of heterogeneous previously published data.…”
mentioning
confidence: 99%